Incomplete Reconstitution of T Cell Subsets on Combination Antiretroviral Therapy in the AIDS Clinical Trials Group Protocol 384 - Gregory K. Robbins; John Spritzler; Ellen S. Chan; David M. Asmuth; Rajesh T. Gandhi; Benigno Rodríguez; Gail Skowron; Paul R. Skolnik; Robert W. Shafer; Richard B. Pollard (2009)
Initiation of combination antiretroviral therapy (ART) results in higher total CD4 cell counts, a surrogate for immune reconstitution. Whether the baseline CD4 cell count affects reconstitution of immune cell subsets has not been well characterized.